2006
DOI: 10.1002/chin.200623007
|View full text |Cite
|
Sign up to set email alerts
|

Giant Electrocaloric Effect in Thin‐Film PbZr0.95Ti0.05O3.

Abstract: Thermal properties D 3000 Giant Electrocaloric Effect in Thin-Film PbZr 0.95 Ti 0.05 O 3 . -Thin films of the title compound (350 nm) exhibit a giant electrocaloric effect of 0.48 K/V at 226°C near the ferroelectric Curie temperature (222°C) exceeding the previously best results obtained in bulk Pb0.99Nb0.02(Zr0.75Sn0.20Ti0.05)0.98O3 (0.003 K/V at 162°C). A large electrocaloric effect may find application in electrical refrigeration and could provide cooling solutions for electronic components such as computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
354
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(366 citation statements)
references
References 1 publication
8
354
1
3
Order By: Relevance
“…[33], the dashed line is a fourth-polynomial method result and the single line represent simulated data using this model. It is found that, the maximum of temperature change ( T  ) is much lower than that reported in work [33], but close to the one reported in Science where a fourth-polynomial was used [31]. In addition, the corresponding maximum of temperature change ( T  ) in our work are near the experiment result, i.e.…”
Section: The Electrocaloric Effectsupporting
confidence: 85%
See 2 more Smart Citations
“…[33], the dashed line is a fourth-polynomial method result and the single line represent simulated data using this model. It is found that, the maximum of temperature change ( T  ) is much lower than that reported in work [33], but close to the one reported in Science where a fourth-polynomial was used [31]. In addition, the corresponding maximum of temperature change ( T  ) in our work are near the experiment result, i.e.…”
Section: The Electrocaloric Effectsupporting
confidence: 85%
“…Usually, when ) (E P hysteresis loops were measured under several selected temperatures, the ) (T P data at selected applied field could be extracted and then the value of ) / ( T P   can be obtained from P versus T by fitting a fourth order polynomial to the data from the upper branches of hysteresis loops [31]. Based on the Maxwell relation, the isothermal entropy change ΔS due to an applied or removal of an electric field is given by:…”
Section: The Electrocaloric Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that a giant ECE could be obtained for thin films because it is possible to apply a higher E. 14,16 ⌬T max = 12 K for PZT thin films near T C = 226°C, 14 and ⌬T max = 5 K for 0.9PMN-0.1PT thin films near 60°C, 16 were determined by indirect measurements using Eq. ͑1͒.…”
mentioning
confidence: 99%
“…18͒ were subsequently found to show ⌬T max = 12 and 4.9 K near T C , respectively, and the entropy ͑and energy͒ changes per cycle in the polymer could be up to five times larger than for PZT. 14 Although progress has therefore been reported in achieving the ECEs at lower operating temperatures, 17 the large 12°C effects 14,17 have not previously been demonstrated at or very near room temperature.…”
mentioning
confidence: 99%